Altruism in nursing from 2012 to 2022: A scoping review - Chen, Yilin; Xie, Caixia; Zheng, Ping; Zeng, Yanli (Frontiers in Psychiatry, 2022)
Abstract Background: Being a nurse with non-altruistic orientation exists and altruism decline is being challenged as never before, which would be a disaster for medicine if left unnoticed. Purpose: To describe the meaning of altruism and altruistic behaviors in nursing, and to discuss dilemmas we face today. Method: Cochrane, PROSPERO, PubMed, Web of Science, CINAHL, Scopus, Embase, ProQuest, and CNKI were searched for original research published in English or Chinese from 2012 to February 2022, on 8 July 2021. Results: By screening 13 studies came from 12 different countries described altruism and altruistic behaviour together were included in. Altruism has been described as value, vocation, or professionalism in nursing which can reflect nurses’ compassion, level of expertise, and quality of care. Altruistic nursing care, body donation, financial endowment, volunteering, sharing, benefiting patients maximum, and helping colleagues represented most of the altruistic behaviours in nursing. There is a vacant that not any assessment tool designed for measuring altruism in nurse groups. Interventions from curriculums in class and support of organizations with psychological methods could be helpful to improve the nurses’ level of altruism. Conclusion: Altruism and altruistic behaviors in the past decades were described. A new concept of altruism in nursing was proposed based on the original meaning and the current changes, and interventions for promoting altruism and some of the dilemmas faced today were synthesized.